Variabilities in Retinal Hemodynamics Across the Menstrual Cycle in Healthy Women Identified Using Optical Coherence Tomography Angiography - Vlad Constantin Donica; Alexandra Lori Donica; Irina Andreea Pavel; Ciprian Danielescu; Anisia Iuliana Alexa; Camelia Margareta Bogdănici (Life)
Background: Numerous conditions, both physiological and pathological, can influence changes in the retinal vascular architecture. In order to be able to highlight pathological aspects of systemic diseases with ocular activity, it is necessary to understand how physiological fluctuations can influence circulation at the retinal level. The present study attempts to evaluate retinal and choroidal vascular and structural changes in healthy female subjects over the course of a menstrual cycle using OCT-A. Methods: We analyzed 22 eyes from healthy reproductive women with a regular menstrual cycle. We performed five OCT-A scans of the subjects every 7–8 days over the course of a month starting from the first day of the menstrual cycle and ending with the first day of the next cycle, measuring perfusion density in the superficial and deep vascular plexuses, choroidal thickness, and FAZ perimeter. Results: There are physiological variations in retinal hemodynamics that can be identified using OCT-A, choroidal thickness having statistically significant increased values in the parafoveal nasal sector during the ovulatory phase (289.18 µm) compared to the early follicular phase (281.9 µm), and the subfoveal sector during the ovulatory phase (319.04 µm) compared to the early follicular phase (308.27 µm). Conclusions: These findings along with abnormally small FAZ perimeters indicate that the menstrual cycle phase should be considered whenever interpreting OCT-A results. Further studies that include larger cohorts, control groups, and hormone serum levels are necessary to confirm and correlate retinal vascular alterations and the phase of the menstrual cycle using OCT-A.